KESEIMBANGAN EMOSI DAN PENGEMBANGAN KREATIFITAS DALAM KAJIAN SENI KALIGRAFI - Fajrina Nashira Ramadhana; Najwa Sakinah Lubis; Rayhan Zulfian Sivara; Irma Irma; Hadid Ray Al Faruq (Jurnal Psikotes, 2025)
Calligraphy art has long been known as a form of artistic expression that not only beautifies writing, but also has therapeutic value in balancing emotions and encouraging the development of individual creativity. This study aims to analyze how calligraphy art can affect emotional balance and support the development of creativity, especially among students and the general public. Using a qualitative approach, this study involved a literature study on the relationship between calligraphy art and human psychology. The results showed that calligraphy practice can improve concentration, reduce stress levels, and improve emotional well-being. In addition, calligraphy art has also been shown to be effective in stimulating creativity, improving abstract thinking skills, and enriching aesthetic understanding. This study proposes that calligraphy art is not only useful in the context of beauty, but also as a potential tool for psychological therapy and creativity development in various fields.